2005
DOI: 10.1302/0301-620x.87b2.14781
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial survival in the interfacial gap in gentamicin-loaded acrylic bone cements

Abstract: Clinical experience indicates the beneficial effects of antibiotic-loaded bone cement. Although in vitro studies have shown the formation of a biofilm on its surface they have not considered the gap between the cement and the bone. We have investigated bacterial survival in that gap. Samples with gaps 200 microm wide were made of different bone cements. These were stored dry ('pre-elution') or submersed in phosphate-buffered saline to simulate the initial release of gentamicin ('post-elution'). The gaps were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 35 publications
0
44
0
4
Order By: Relevance
“…36 The bacteria that survived on the NT surface could lead to implant infection; especially when the NT surface was covered with protein. The in vitro study may predict that the NTs cannot prevent implant infection in vivo.…”
mentioning
confidence: 99%
“…36 The bacteria that survived on the NT surface could lead to implant infection; especially when the NT surface was covered with protein. The in vitro study may predict that the NTs cannot prevent implant infection in vivo.…”
mentioning
confidence: 99%
“…One of the prophylactic strategies that are currently used is to provide a constant flow of a subinhibitory (sub-MIC) concentration of antibiotic (17). Another alternative is to use biomaterials impregnated with antibiotic (21,32). However, besides the reduced abilities of bacteria to form biofilms, little is known about other changes implicated in the virulence of CoNS that might occur due to the presence of low concentrations of antibiotics.…”
mentioning
confidence: 99%
“…The exact mechanism by which this antibiotic resistance evolves is not clear and different options have been reported, including 24 stated that gentamicin-loaded bone cement has an optimum surface for bacterial colonization and prolonged exposure to gentamicin allows mutational resistance to occur. However, it is important to realize that antibiotics probably do not directly cause mutation; rather, they provide an environment favoring the natural selection of resistant strains 3,25 that arise spontaneously. The drug kills the sensitive bacteria, leaving behind those that can resist it.…”
Section: Discussionmentioning
confidence: 99%
“…In a more clinically relevant situation, the volume-to-area ratio is very small, however, for which reason we developed our so-called ''interfacial gap'' model, in which the amount of fluid in between the surfaces to be colonized is small. 25 This model, simulating the in vivo interfacial gap, existing between bone cement and bone or prosthesis, offers an additional in vitro test that can be used to estimate the value of antibiotic additions to bone cement. 19,25 Hendriks et al 19 demonstrated that concentrations up to 1000-fold the antibiotic resistance levels for most bacterial strains causing implant infection can be achieved in this more realistic in vitro model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation